Exchange Rate Regime Choice in Historical Perspective - Bordo, Michael (IMF Working Papers; Working Paper, 2003)
In this paper, I survey the issue of exchange rate regime choice from the perspective of both the industrial and emerging economies taking an historical perspective. I first survey the theoretical issues beginning with a taxonomy of regimes. I then examine the empirical evidence on the delineation of regimes and their macroeconomic performance. The penultimate section provides a brief history of monetary regimes in industrial and emerging economies. The conclusion considers the case for a managed float regime for today's emerging economies.